Socio-economic transformation of small towns in East Germany after 1990 - Colditz case study - Cudny, Waldemar (Bulletin of Geography. Socio-economic Series, 2012)
The article presents the main demographic and social, as well as functional and spatial changes that took place in Colditz after 1990. The town is inhabited by 4,870 people (2009) and is situated in Saxony, in the area of the former German Democratic Republic (GDR). The aim of the article is to present the main changes, which took place there after East and West Germany reunited in 1990. The author describes demographic and social changes in the population size, population growth, migration balance, unemployment, and other elements of urban community. Moreover, the article presents the changes in the economic-functional structure, such as de-industrialisation, succession of urban functions, and tourism development, as well as the main spatial changes in Colditz, such as architectural revitalisation and reconstruction of urban infrastructure. In the conclusions, the author briefly presents potential directions in the future development of the town.